2022
DOI: 10.24018/ejmed.2022.4.6.1609
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Interferential Current for the Treatment of Chronic Low Back Pain

Abstract: Background: The problem of pain in the lumbar region is a big part of physiotherapy, which aims not only to relieve patients from pain but also to restore them to their previous levels of functionality. Various interventions are used for this physiotherapy treatment, one of them is electrotherapy. This review aims to investigate the effectiveness of interferential current (IFC) in pain management in patients with chronic low back pain (CLBP). Methods: A search was conducted in electronic databases Google Sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
0
0
Order By: Relevance
“…They underscored the potential of these techniques to be widely utilized in clinical settings to enhance hamstring flexibility [ 4 ]. Theologou et al established through their research that the application of interferential current could contribute to pain reduction and enhance functionality, body posture, walking ability, and balance among patients with CLBP [ 18 ]. Vincenzino et al suggested that the prompt pain-relieving effects of Mulligan’s techniques could be attributed to the activation of non-opioid endogenous pain inhibition pathways.…”
Section: Discussionmentioning
confidence: 99%
“…They underscored the potential of these techniques to be widely utilized in clinical settings to enhance hamstring flexibility [ 4 ]. Theologou et al established through their research that the application of interferential current could contribute to pain reduction and enhance functionality, body posture, walking ability, and balance among patients with CLBP [ 18 ]. Vincenzino et al suggested that the prompt pain-relieving effects of Mulligan’s techniques could be attributed to the activation of non-opioid endogenous pain inhibition pathways.…”
Section: Discussionmentioning
confidence: 99%